1983
DOI: 10.1136/bjo.67.7.487
|View full text |Cite
|
Sign up to set email alerts
|

Steroid responsiveness in connective tissue diseases.

Abstract: Thirty-four patients with connective tissue diseases used dexamethasone drops 01% in one eye for 6 weeks. There was a higher incidence of positive steroid response than would be expected in a normal population. Most of the male patients were responders. Care should be exercised when prescribing local steroids for these patients. Males should be offered regular screening for glaucoma. Eye involvement is a prominent feature of connective tissue diseases (CTD). Keratoconjunctivitis sicca (KCS) is the commonest co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 4 publications
0
20
0
2
Order By: Relevance
“…In a study of 34 patients with connective tissue disease, mainly rheumatoid arthritis, who used 0.1% dexamethasone drops in one eye for 6 weeks, Gaston et al [45] reported a higher incidence of positive steroid response than would be expected in a normal population. Additionally, most of the male patients were responders.…”
Section: Connective Tissue Disease and Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 34 patients with connective tissue disease, mainly rheumatoid arthritis, who used 0.1% dexamethasone drops in one eye for 6 weeks, Gaston et al [45] reported a higher incidence of positive steroid response than would be expected in a normal population. Additionally, most of the male patients were responders.…”
Section: Connective Tissue Disease and Sexmentioning
confidence: 99%
“…The possibility of high response is greater in the following cases: patients with primary open-angle glaucoma (POAG) or glaucoma suspects, first-degree relatives with POAG [44] , old age or age less than 6 years, connective tissue disease, especially rheumatoid arthritis in men [45] , high myopia [46,47] , type 1 diabetes mellitus [37,48] , and angle recession glaucoma [49] . Patients with predisposing risk factors should be monitored more diligently when receiving corticosteroids.…”
Section: Risk Factorsmentioning
confidence: 99%
“…It has been reported that there is a greater risk of corticosteroid response in patients with certain types of connective tissue disease, 9 type I diabetes, 10 a first-degree relative with primary open-angle glaucoma (POAG), [11][12][13] or high myopia. 14,15 Other steroid-induced ocular effects that have been reported include an increase in corneal thickness and a slight mydriasis, but these changes have not been shown to correlate with an ocular hypertensive response.…”
Section: Other Factorsmentioning
confidence: 99%
“…IOP levels exceeded 31 mm Hg [2,3] . An elevation in IOP in response to corticosteroid therapy is more frequently observed in patients with primary open-angle glaucoma (POAG) [4,5] and a positive family history for POAG [6] , in children (especially under the age of 6 years) [7] , and in patients with type 1 diabetes mellitus [8] , high myopia [9] , connective tissue disease (especially rheumatoid arthritis) [10] and angle recession [11] . A moderate increase in IOP can be observed in 18-36% of the general population in response to topical corticosteroid treatment, whereas only 5-6% of the general population versus 46-92% of patients with POAG will have a significant and potentially harmful increase in IOP [4,5,[12][13][14] .…”
Section: Introductionmentioning
confidence: 99%